COVID-19 and how best to complete the 2019-2020 football season - Jones, M.; Hardman, A. (Philosophy, Sport, and the Pandemic, 2022)
The purpose of this chapter is to analyze the impact of COVID-19 on the football world and examine how distributive justice in terms of the relevant difference principle, has been interpreted to determine the outcome of European competitions/leagues for the 2019-2020 football season. The three methods examined are (a) completing the season by playing the remaining games behind closed doors, i.e., without fans; (b) determining the outcome of a season using the Points Per Game (PPG) formula, and (c) to cancel the season and declare it "null and void." The chapter indicates that there is merit to each of the positions considered but aims for a position that strikes the best balance between safeguarding people's health and well-being, assisting the economy, and at the same time, can ensure that principles of fairness and justice are maintained. It concludes that the only fair and just way to decide the 2019-2020 season was to complete the games behind closed doors.